Phosphatidyl Inositol 3 Kinase-Gamma Balances Antiviral and Inflammatory Responses During Influenza A H1N1 Infection: From Murine Model to Genetic Association in Patients - Garcia, Cristiana C.; Tavares, Luciana P.; Dias, Ana Carolina F.; Kehdy, Fernanda; Alvarado-Arnez, Lucia Elena; Queiroz-Junior, Celso M.; Galvão, Izabela; Lima, Braulio H.; Matos, Aline R.; Gonçalves, Ana Paula F.; Soriani, Frederico M.; Moraes, Milton O.; et al. (Frontiers in Immunology, 2018)
: Influenza A virus (IAV) infection causes severe pulmonary disease characterized by intense leukocyte infiltration. Phosphoinositide-3 kinases (PI3Ks) are central signaling enzymes, involved in cell growth, survival and migration. Class IB PI3K or PI3Kγ, mainly expressed by leukocytes, are involved in cell migration during inflammation. Here, we investigated the contribution of PI3Kγ for the inflammatory and antiviral responses to IAV. PI3Kγ knock out (KO) mice were highly susceptible to lethality following infection with influenza A/WSN/33 H1N1. In the early time points of infection, infiltration of neutrophils was higher than WT mice whereas type I and type II IFN expression and p38 activation were reduced in PI3Kγ KO mice resulting in higher viral loads when compared to WT mice. Blockade of p38 in WT macrophages infected with IAV reduced levels of interferon-stimulated gene 15 (ISG15) protein to those induced in PI3Kγ KO macrophages, suggesting that p38 is downstream of antiviral responses mediated by PI3Kγ. PI3Kγ KO-derived fibroblasts or macrophages showed reduced type-I IFN transcription and altered pro-inflammatory cytokines suggesting a cell autonomous imbalance between inflammatory and antiviral responses. Seven days after IAV infection, there were reduced infiltration of Natural Killer (NK) cells and CD8+ T lymphocytes, increased concentration of inflammatory cytokines in bronchoalveolar fluid, reduced numbers of resolving macrophages and IL-10 levels in PI3Kγ KO. This imbalanced environment in PI3Kγ KO infected mice culminated in enhanced lung neutrophil infiltration, Reactive Oxygen Species (ROS) release and lung damage that together with the increased viral loads, contributed to higher mortality in PI3Kγ KO mice compared to WT mice. In humans, we tested the genetic association of disease severity in influenza A/H1N1pdm09 infected patients with three potentially functional PIK3CG single nucleotide polymorphisms (SNPs), rs1129293, rs17847825 and rs2230460. We observed that SNPs rs17847825 and rs2230460 (A and T alleles, respectively) were significantly associated with protection from severe disease using the recessive model in patients infected with influenza A(H1N1)pdm09. Altogether, our results suggest that PI3Kγ is crucial in balancing antiviral and inflammatory responses to IAV infection.